Intraspecific crossability and compatibility within Solanum aethiopicum - Buteme, Ruth; Nakajiri, Mary; Kucel, Newton; Nahamya Kabod, Pamela; Sseremba, Godfrey; Balyejusa Kizito, Elizabeth (Heliyon, 2021)
Understanding hybridization barriers is relevant for germplasm conservation and utilization. The prezygotic barriers to hybridization include floral morphological differences like pistil and stamen length, pollen characteristics and pollen-pistil interactions. This study sought to elucidate the reproductive biology of Solanum aethiopicum; its mating systems and compatibility barriers. Eight genotypes of Solanum aethiopicum were examined for differences in floral morphology, phenology and cross compatibility in a full diallel mating design, with assessment of fruit set, seed set and seed viability. In-vivo pollen tube growth was observed for failed crosses at 24, 48 and 72 h after pollination. All genotypes had heterostyly flowers, with predominantly small white petals. Incompatibility was observed in five out of 39 combinations. All selfed genotypes displayed compatibility implying the genotypes are self-compatible. Pollen–pistil incompatibility, which was exhibited in four out of the five failed cross combinations, occurred on the stigma, upper style and lower style, a phenomenon typical in Solanaceae. Solanum aethiopicum is self-compatible and majorly self-pollinating but has features that support cross-pollination.
Keywords: Pollen viability in vitro; Pollen tube growth in vivo; Pollen-pistil interaction; Style exsertion; Intraspecific hybridization; Solanum aethiopicum